Vietnam a long history - Nguyễn Khắc Viện. (Hà Nội : Thế giới, 1999)
This book is talking about Vietnam's history. Its contents incluse two parts: Traditional Vietnam and contemporary Vietnam (1958-1990s)
Keywords: Vietnam; History; Vietnam -- History; Vietnam -- History